An empirical analysis of search costs and price dispersion - Joshua Sherman; Avi Weiss (Bar-Ilan University, Department of Economics, 2014)
We exploit cross-sectional and temporal differences in search intensity in order to examine the relationship between search costs and price dispersion using a hand-collected panel data set from Jerusalem's Shuk Mahane Yehuda outdoor market. We present empirical evidence that price dispersion increases with the cost of search using several different measures of price dispersion, however, our interpretation of this finding is sensitive to the search proxy in question. We also address several acute difficulties facing empiricists seeking to test theoretical price-dispersion models in which consumers are heterogeneous in their search behavior.
Keywords: L11; L13; 330